Availability and affordability of children essential medicines in health facilities of southern nations, nationalities, and people region, Ethiopia: key determinants for access - Tefera Tadesse; Habtamu Abuye; Gizachew Tilahun (BMC, 2021)
Abstract Background Children in resource-limited countries are more likely to die from treatable conditions than those in higher resource settings due to a lack of the right essential medicine at the right time. Globally millions of children die every year from conditions that could be treatable with existing medicines before they reach their fifth birthday. This study aimed in assessing the availability and affordability of essential medicine for children in selected health facilities of southern nations, nationalities, and peoples' regions (SNNPR), Ethiopia. Method A medicine outlets-based cross-sectional study was conducted to assess the availability, affordability, and prices of the 30 selected essential medicines (EMs) for children in 30 public and 30 private medicine outlets in SNNPR from March 29 to May 5, 2019, applying WHO and Health Action International (HAI) tools. Availability was expressed as the percentage of sampled medicine outlets per sector that the surveyed medicine was found on the day of data collection. The amount of daily wages required for the lowest-paid government unskilled worker (LPGW) to buy one standard treatment of an acute condition or treatment for a chronic condition for a month was used to measure affordability and median price ratio for the price of EMs. The results Availability varied by sector, type of medication, and level of health facilities. The average availability of EM was 57.67% for the public sector and 53.67% for the private sector. Ceftriaxone, SOR, zinc sulfate, and cotrimoxazole were the most widely available types of medications in the two sectors. The median price ratios (MPR) for the cheapest drugs LP were 1.26 and 2.24 times higher than their International Reference Price (IRP) in the public and private sectors respectively. Eighty-two percent of LP medicines in the public and 91 % of LP medicines in the private sectors used in the treatments of prevalent common conditions in the region were unaffordable as they cost a day's or more wages for the LPGW. Conclusion Availability, affordability, and price are determinant pre-requisite for EMs access. According to the current work, although fair availability was achieved, the observed high price affected affordability and hence access to EMs.